Daily mycoprotein consumption for 1 week does not affect insulin sensitivity or glycaemic control but modulates the plasma lipidome in healthy adults: a randomised controlled trial. Issue 2 (28th January 2021) - Coelho, Mariana O. C.; Monteyne, Alistair J.; Dirks, Marlou L.; Finnigan, Tim J. A.; Stephens, Francis B.; Wall, Benjamin T.
Abstract: Mycoprotein consumption has been shown to improve acute postprandial glycaemic control and decrease circulating cholesterol concentrations. We investigated the impact of incorporating mycoprotein into the diet on insulin sensitivity (IS), glycaemic control and plasma lipoprotein composition. Twenty healthy adults participated in a randomised, parallel-group trial in which they consumed a 7 d fully controlled diet where lunch and dinner contained either meat/fish (control group, CON) or mycoprotein (MYC) as the primary source of dietary protein. Oral glucose tolerance tests were performed pre- and post-intervention, and 24 h continuous blood glucose monitoring was applied throughout. Fasting plasma samples were obtained pre- and post-intervention and were analysed using quantitative, targeted NMR-based metabonomics. There were no changes within or between groups in blood glucose or serum insulin responses, nor in IS or 24 h glycaemic profiles. No differences between groups were found for 171 of the 224 metabonomic targets. Forty-five lipid concentrations of different lipoprotein fractions (VLDL, LDL, intermediate-density lipoprotein and HDL) remained unchanged in CON but showed a coordinated decrease (7–27 %; all P < 0·05) in MYC. Total plasma cholesterol, free cholesterol, LDL-cholesterol, HDL2-cholesterol, DHA and n -3 fatty acids decreased to a larger degree in MYC (14–19 %) compared with CON (3–11 %; P < 0·05). Substituting meat/fish for mycoprotein twice daily for 1 week did not modulate whole-body IS or glycaemic control but resulted in changes to plasma lipid composition, the latter primarily consisting of a coordinated reduction in circulating cholesterol-containing lipoproteins.